KL-6 in acute lung injury: will it leave its mark? - Shyamsundar, Murali (BioMed Central, 2008)
Studies have indicated that measuring biochemical measures of epithelial injury in plasma and alveolar fluid may be useful in predicting outcome in acute lung injury. The present commentary briefly reviews the evidence supporting the use of these biochemical biomarkers of epithelial injury in acute lung injury, and in particular KL-6, as well as their limitations. The article additionally proposes the need for physiological markers of epithelial function to complement current biochemical biomarkers.